Alkyne-Forming Furan Fragmentation: A General Method to Convert Furans into Alkynoic Acids - Deng, Jiachen; Gui, Jinghan (Synlett, 2019)
Furans are readily available and highly reactive heterocycles that serve as versatile four-carbon synthons in organic synthesis. Recently, we discovered that furans, upon oxidation with singlet oxygen, can be transformed into alkynes via dual C–C double-bond cleavage. This Synpacts article presents an overview of the historical context and the development of this furan fragmentation reaction. We also discuss its application in natural product synthesis and a plausible reaction mechanism.1 Introduction2 Background of Alkyne-Forming Furan Fragmentation3 Reaction Development4 Conclusion
Keywords: furans; alkynes; singlet oxygen; fragmentation; cycloaddition; ring strain; natural products